2021
DOI: 10.1039/d0sc06466a
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ammonia and hydrazine by electron rich Fe(ii) complexes supported by a dianionic pentadentate ligand platform through a common terminal Fe(iii) amido intermediate

Abstract: Synopsis: a highly reactive Fe(iii)–NH2 complex is generated via activation of ammonia or hydrazine in reactions of relevance to fundamental steps in ammonia oxidation processes mediated by an abundant, first row transition metal.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 81 publications
(166 reference statements)
2
26
1
Order By: Relevance
“…NMR line shape simulation of this AA′XX′ system provides coupling constants 1 J NH = −64 Hz, 2 J NH = 1 Hz, 1 J NN = 10 Hz, and 3 J HH = 23 Hz (Figure S11). The vicinal 3 J HH coupling is within the range of reported in previously characterized diazene complexes ( 3 J HH = 21–30 Hz). ,, Moreover, other diamagnetic C 2 -symmetric 15 N-labeled diazene complexes such as [(B 2 Pz 4 Py)­Fe]­(μ-N 2 H 2 ) and [PhBP CH 2 Cy 3 ]­Fe­(OAc)} 2 (μ-N 2 H 2 ) also exhibit characteristic AA′XX′ signals in 1 H NMR spectra.…”
Section: Results and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…NMR line shape simulation of this AA′XX′ system provides coupling constants 1 J NH = −64 Hz, 2 J NH = 1 Hz, 1 J NN = 10 Hz, and 3 J HH = 23 Hz (Figure S11). The vicinal 3 J HH coupling is within the range of reported in previously characterized diazene complexes ( 3 J HH = 21–30 Hz). ,, Moreover, other diamagnetic C 2 -symmetric 15 N-labeled diazene complexes such as [(B 2 Pz 4 Py)­Fe]­(μ-N 2 H 2 ) and [PhBP CH 2 Cy 3 ]­Fe­(OAc)} 2 (μ-N 2 H 2 ) also exhibit characteristic AA′XX′ signals in 1 H NMR spectra.…”
Section: Results and Discussionsupporting
confidence: 84%
“…The trends in ν­(NN) vibrational frequencies across this series underscore the need for an alternative to traditional H-bonding in which the strongest H-bond acceptor in 2d would lead to the largest difference in ν­(NN) from 3 that lacks any H-bond acceptor. We also note that the ν­(NN) frequencies observed across the 2a – 2d series (1419–1398 cm –1 ) in comparison to 3 (1353 cm –1 ) span a significant portion of known diazene ligand ν­(NN) frequencies, which range from 1321 cm –1 for an electron-rich [(B 2 Pz 4 py)­Fe] 2 (μ-N 2 H 2 ) complex to 1419 cm –1 for 2a . In particular, complexes 2a – 2d in conjunction with 3 illustrate the ability to dramatically tune the degree of NN activation through second-sphere interactions.…”
Section: Results and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…90 This represents an attractive alternative to the H-bonding methods of stabilization noted above and provides opportunities for the study of intermediates that are relevant to the nitrogen cycle. [91][92][93][94][95] Lewis acid SCSs are often installed post metal coordination to avoid quenching of the ligand lone pairs. Exemplar of this notion, Szymczak and co-workers showed that iron could be coordinated to a pyridine(dicarbene) pincer ligand and subsequently hydroborated.…”
Section: Diboranyl Pincer Ligandsmentioning
confidence: 99%
“…The irreversible binding of NH 3 , or its reactivity with the metal complex, may also constitute an important disadvantage in catalyst design. Despite the inherent stability of the N–H bonds in NH 3 , activation under mild conditions can occur through ligand–metal cooperation, 9 where the presence of basic ligands can result in the redox-neutral heterolysis of NH 3 and subsequent ligand protonolysis. Facile N–H activation of NH 3 via metal–ligand cooperative addition was also reported in one instance for a uranium complex.…”
Section: Introductionmentioning
confidence: 99%